ANTIBACTERIAL ACTIVITY TEST OF MIANA (COLEUS ATROPURPUREUS L.) LEAF ETHANOL EXTRACT AGAINST STAPHYLOCOCCUS EPIDERMIDIS FNCC 0048 AND ESCHERICHIA COLI FNCC 0091 - Maulana Tegar Aditya Nugraha; Arviani; Lubna Hanifah (Jurnal Kesehatan, 2022)
Infection is one of the health problems that is often experienced by the community, among others, infectious diseases that can be caused by Staphylococcus epidermidis and acute diarrheal diseases that can be caused by Escherichia coli bacteria. One of the plants that has antibacterial properties is Miana leaf (Coleus atropurpureus L.) because they contain active compositions containing essential oils, steroids, tannins, flavonoids, and alkaloids. This aims of this research were to study antibacterial activity and minimum concentration of ethanol extract of Miana leaf (Coleus atropurpureus L.) that gives antibacterial activity against Staphylococcus epidermidis and Escherichia coli. This type of research is an experimental research, using the method of well diffusion and diameter of the inhibition zone. The different concentrations of Miana leaf ethanol extract were used at 3%, 6%, and 9%. Tests were carried out to observe the presence or absence of inhibitory zones of Miana leaf (Coleus atropurpureus L.) extracts against Staphylococcus epidermidis and Escherichia coli after 24 hours of incubation. The analysis used is descriptive analysis. The results showed that the ethanol extracts of Miana leaf (Coleus atropurpureus L.) with concentrations of 3%, 6%, and 9% are able to inhibit the growth of Staphylococcus epidermidis. The minimum concentration of ethanol extract of Miana leaf which shows antibacterial activity against test bacteria is 3%.